2003
DOI: 10.1038/sj.npp.1300375
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Corticotropin-Releasing Factor and Perceived Early-Life Stress in Depressed Patients and Healthy Control Subjects

Abstract: Previous studies have reported elevated concentrations of cerebrospinal fluid (CSF) corticotropin-releasing factor (CRF) in patients with major depression. Elevations of CSF CRF have also been reported in adult laboratory animals exposed to the stress of brief maternal deprivation or maternal neglect in the neonatal or preweaning period. The present study was designed to determine whether major depression and a history of perceived early adversity in childhood are independently associated with elevated CSF CRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
104
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(123 citation statements)
references
References 45 publications
16
104
1
Order By: Relevance
“…Although it could also be argued that PD subjects, who score higher on measures of stress reactivity such as neuroticism, are more sensitive than other subjects to the psychological stress of lumbar puncture. Mean CRF concentration in the PD group (39.9727.8 pg/ml) was comparable to those reported previously in clinical populations with depression (Carpenter et al, 2004), anxiety disorder (Fossey et al, 1996), acute alcohol withdrawal (Adinoff et al, 1996), schizophrenia (Nishino et al, 1998), in PTSD with and without psychosis (Sautter et al, 2003), and as measured by serial sampling in PTSD (Baker et al, 1999). It is of interest that CRF values in our normal controls (27.1713.2 pg/ml) are comparable to those reported by Carpenter et al (2004) (24.978.6 pg/ml).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Although it could also be argued that PD subjects, who score higher on measures of stress reactivity such as neuroticism, are more sensitive than other subjects to the psychological stress of lumbar puncture. Mean CRF concentration in the PD group (39.9727.8 pg/ml) was comparable to those reported previously in clinical populations with depression (Carpenter et al, 2004), anxiety disorder (Fossey et al, 1996), acute alcohol withdrawal (Adinoff et al, 1996), schizophrenia (Nishino et al, 1998), in PTSD with and without psychosis (Sautter et al, 2003), and as measured by serial sampling in PTSD (Baker et al, 1999). It is of interest that CRF values in our normal controls (27.1713.2 pg/ml) are comparable to those reported by Carpenter et al (2004) (24.978.6 pg/ml).…”
Section: Discussionsupporting
confidence: 85%
“…This is accounted for by the significant restriction of range in PBI Care scores to the higher end in normal, non-PD samples; a larger sample would be necessary to adequately address the relationship between parental care and adult CSF CRF levels in normal controls. Of note, a previous investigation did find a relationship between CSF CRF and a different measure of early life stress in healthy volunteers not screened for PD (Carpenter et al, 2004). If PD does not determine CSF CRF level, what is the clinical relevance of CSF CRF in PD?…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…CRF appears to be important to the pathophysiology of stress-related disorders such as post-traumatic stress disorder (PTSD) and depression; elevated levels of cerebrospinal fluid (CSF) CRF have been identified in both of these disorders (Bremner et al, 1997;Gold and Chrousos, 2002). Early life stress has also been associated with alterations in adult CSF CRF levels, in both preclinical and clinical studies (Carpenter et al, 2004;Heim et al, 2004), and recent study results indicate that that early life stress influences stress system function in adults with FM (McLean et al, 2005b;Weissbecker et al, 2005). In the single study assessing CRF levels in FM patients to date, Riedel et al (2002) found higher baseline serum CRF levels in FM patients vs healthy controls.…”
Section: Introductionmentioning
confidence: 99%